GROWTH AND YIELD OF SHALLOTS PLANTED BETWEEN CHILI PLANTS - muhammad ansar; Imam Wahyudi; Dance Tangkesalu (AGROLAND: The Agricultural Sciences Journal, 2019)
Community needs for the shallot commodity take place regularly every day because it is a food flavoring ingredient. For this reason, it needs to be followed by the availability of production supplies that are in accordance with consumer needs. Sigi Regency is one of the centers of shallot and chili production in Central Sulawesi, so far it has not been able to make a real contribution in meeting the needs of the community which tends to increase. This is because the exploitation of shallots and chillies is still monoculture, so the risk of crop failure, production decline and farmers' losses is very high. This research was carried out with the aim to determine the growth and yield of shallots planted with various cropping patterns mong chillies, so that information on suitable cropping patterns can be obtained to ensure the availability of high yields of shallots and chillies to meet community needs. The results showed that (i) various shallot cropping patterns among chilli plants did not significantly affect the greenness of leaves, tuber length, fresh weight per tuber, fresh weight of tuber per clump, harvest index and moisture content of shallot bulbs; (ii) leaf length, harvest age and fresh tuber weight of onion bulbs per hectare planted with different cropping patterns among chilli plants were not significantly different, except with monoculture shallot cropping patterns obtained by longer leaves, shorter harvest age (62.0 days) and the weight of fresh bulbs per hectare is higher (1.83 t / ha) compared to various shallot cropping patterns among chilli plants.